2022
DOI: 10.1111/tbed.14503
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and evolutionary dynamics analysis of porcine delta‐coronavirus with host expansion to humans

Abstract: From 2003 onwards, three pandemics have been caused by coronaviruses: severe acute respiratory syndrome coronavirus (SARS‐CoV); middle east respiratory syndrome coronavirus (MERS‐CoV); and, most recently, SARS‐CoV‐2. Notably, all three were transmitted from animals to humans. This would suggest that animals are potential sources of epidemics for humans. The emerging porcine delta‐coronavirus was reported to infect children. This is a red flag that marks the ability of PDCoV to break barriers of cross‐species t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Li et al (2022) suggested that the accumulated mutations in the S gene may enhance dynamics movements and transmission of PDCoV. The recent PDCoV isolates are more adaptable to humans than the early PDCoV strains, indicating that PDCoV gradually adapted to humans by the evolution processes, but further biological assays are needed to confirm this conclusion.…”
mentioning
confidence: 99%
“…Li et al (2022) suggested that the accumulated mutations in the S gene may enhance dynamics movements and transmission of PDCoV. The recent PDCoV isolates are more adaptable to humans than the early PDCoV strains, indicating that PDCoV gradually adapted to humans by the evolution processes, but further biological assays are needed to confirm this conclusion.…”
mentioning
confidence: 99%
“…It is reported that frequent recombination between different lineages may result in the emergence of PDCoV strains with divergent pathogenicity and host tropism ( 1 , 32 ). PDCoV as a novel coronavirus has been reported to infect humans, suggesting that PDCoV has potential to proceed interspecies transmission or evolute as a new human strain ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated the ability of CoVs to spread across species and become zoonotic viruses [ 36 , 37 , 38 ]. As an economically important animal for humans, pigs may serve as a container for SeCoVs and other CoVs and thus spread them to other organisms [ 21 , 39 ]. Therefore, increased surveillance and research on pigs are needed to prevent future pandemics of CoVs.…”
Section: Discussionmentioning
confidence: 99%